Formulas to determine fabric bending rigidity from simple tests. Issue 8 (May 2015) - Plaut, Raymond H
Formulas are derived for effective bending rigidity and bending length, based on the deformation of fabric strips in simple tests. The nine types of tests (including some new ones) involve a cantilever, heart loop, hanging pear loop, hanging ring, free fold, clamped fold, standing wrinkle (buckle), hanging wrinkle, and standing ring. No loads are applied and no special equipment is needed. Only the height of the deformed strip needs to be measured, along with the strip's length, width, and weight. The results can be applied with different lengths of strips and different orientations (e.g., weft, warp, and bias directions). In the analysis, the fabric strip is modeled as an inextensible elastica. Polynomial approximations are developed that give the value of a nondimensional weight parameter (involving the weight, length, width, and bending rigidity) as a function of the height-to-length ratio. The bending rigidity and bending length can then be directly computed.